Single molecule tracking of the molecular mobility in thinning liquid films on thermally grown SiO2 - Täuber, Daniela; Heidernätsch, Mario; Bauer, Michael; Radons, Günter; Schuster, Jörg; Borczyskowski, Christian von (Diffusion Fundamentals, 2009)
Diffusion coefficients obtained from weighted mean square displacements along probe molecule trajectories within ultrathin liquid TEHOS films show a correlation with film thickness. By studying cumulative distributions obtained with a time resolution of 20 ms, we could show that the diffusion is heterogeneous within our liquid films which consist of a few molecular layers only. We detected two components of the diffusion process, a slower and a faster one. Thinning of the film due to evaporation caused a slowdown of the whole diffusion process. But this resulted not from a slowdown in the two contributing components itself. Instead their relative contributions changed in favor for the slow component. We conclude that there is no pronounced difference in the diffusion coefficients attributed to the molecular layers 3 to 5 vertically above the substrate, but with the loss of upper layers along with the thinning process the concentration of probe molecules in the near surface region containing only one or two molecular layers is increased.